Thiophene/selenophene-based S-shaped double helicenes: regioselective synthesis and structures - Wang, Mengjie; Dang, Lanping; Xu, Wan; Ma, Zhiying; Shao, Liuliu; Wang, Guangxia; Li, Chunli; Wang, Hua (Beilstein Journal of Organic Chemistry, 2022)
2,5-Di(trimethylsilanyl)dithieno[2,3-b:3′,2′-d]thiophene ((TMS)2-bb-DTT), 2,5-di(trimethylsilanyl)diseleno[2,3-b:3′,2′-d]thiophene ((TMS)2-bb-DST), and 2,5-di(trimethylsilanyl)diseleno[2,3-b:3′,2′-d] selenophene ((TMS)2-bb-DSS) were used as starting materials to synthesize three S-shaped double helicenes (i.e., DH-1, DH-2, and DH-3) through monobromination, formylation, the Wittig reaction, and double oxidative photocyclization. The photocyclization was a highly regioselective process. The molecular structures of DH-1 and DH-2 were confirmed by X-ray single-crystal analysis. Multiple intermolecular interactions, such as C–S, C–Se, S–S, S–Se, and Se–Se, were observed in the crystal packing structures of these compounds. Spectroscopic results and our previous work showed that the combination of molecular structure change and heteroatom replacement from S to Se could precisely modulate molecular energy levels.
Keywords: crystal structure; double helicene; regioselective synthesis; selenophene; thiophene

(untitled) - Mori, T. (Chem. Rev., 2021)

(untitled) - Dhbaibi, K.; Favereau, L.; Crassous, J. (Chem. Rev., 2019)

(untitled) - Rickhaus, M.; Mayor, M.; Juríček, M. (Chem. Soc. Rev., 2016)

(untitled) - Hoffmann, N. (J. Photochem. Photobiol., C, 2014)

(untitled) - Gingras, M. (Chem. Soc. Rev., 2013)

(untitled) - Shen, Y.; Chen, C.-F. (Chem. Rev., 2012)

(untitled) - Urbano, A. (Angew. Chem., Int. Ed., 2003)

(untitled) - Katz, T. J. (Angew. Chem., Int. Ed., 2000)

(untitled) - Miyasaka, M.; Rajca, A. (Synlett, 2004)

(untitled) - Zhang, C.; Ma, Z.; Wang, G.; Li, C.; Wang, H. (Org. Chem. Front., 2020)

(untitled) - Rajca, A.; Wang, H.; Pink, M.; Rajca, S. (Angew. Chem., Int. Ed., 2000)

(untitled) - Li, C.; Shi, J.; Xu, L.; Wang, Y.; Cheng, Y.; Wang, H. (J. Org. Chem., 2009)

(untitled) - Liu, X.; Sun, H.; Xu, W.; Wan, S.; Shi, J.; Li, C.; Wang, H. (Org. Chem. Front., 2018)

(untitled) - Rajca, A.; Miyasaka, M.; Pink, M.; Wang, H.; Rajca, S. (J. Am. Chem. Soc., 2004)

(untitled) - Miyasaka, M.; Pink, M.; Olankitwanit, A.; Rajca, S.; Rajca, A. (Org. Lett., 2012)

(untitled) - Miyasaka, M.; Rajca, A.; Pink, M.; Rajca, S. (J. Am. Chem. Soc., 2005)

(untitled) - Wang, J.; Wang, G.; Li, C.; Dong, Y.; Ma, Z.; Wang, H. (J. Org. Chem., 2021)

(untitled) - Li, C.; Wu, L.; Xu, W.; Song, J.; Shi, J.; Yu, P.; Kan, Y.; Wang, H. (J. Org. Chem., 2015)

(untitled) - Wang, Z.; Shi, J.; Wang, J.; Li, C.; Tian, X.; Cheng, Y.; Wang, H. (Org. Lett., 2010)

(untitled) - Hollinger, J.; Gao, D.; Seferos, D. S. (Isr. J. Chem., 2014)

(untitled) - Patra, A.; Bendikov, M. (J. Mater. Chem., 2010)

(untitled) - Okamoto, T.; Kudoh, K.; Wakamiya, A.; Yamaguchi, S. (Org. Lett., 2005)

(untitled) - Yamamoto, T.; Takimiya, K. (J. Am. Chem. Soc., 2007)

(untitled) - Izawa, T.; Miyazaki, E.; Takimiya, K. (Chem. Mater., 2009)

(untitled) - Pao, Y.-C.; Chen, Y.-L.; Chen, Y.-T.; Cheng, S.-W.; Lai, Y.-Y.; Huang, W.-C.; Cheng, Y.-J. (Org. Lett., 2014)

(untitled) - Lee, C.-H.; Lai, Y.-Y.; Cheng, S.-W.; Cheng, Y.-J. (Org. Lett., 2014)

(untitled) - Xu, W.; Wu, L.; Fang, M.; Ma, Z.; Shan, Z.; Li, C.; Wang, H. (J. Org. Chem., 2017)

(untitled) - Xu, W.; Wang, M.; Ma, Z.; Shan, Z.; Li, C.; Wang, H. (J. Org. Chem., 2018)

(untitled) - Schwartz, P.-O.; Förtsch, S.; Vogt, A.; Mena-Osteritz, E.; Bäuerle, P. (Beilstein J. Org. Chem., 2019)

(untitled) - Liu, X.; Yu, P.; Xu, L.; Yang, J.; Shi, J.; Wang, Z.; Cheng, Y.; Wang, H. (J. Org. Chem., 2013)

(untitled) - Pino-Rios, R.; Yañez, O.; Inostroza, D.; Ruiz, L.; Cardenas, C.; Fuentealba, P.; Tiznado, W. (J. Comput. Chem., 2017)

(untitled) - Fu, R.; Lu, T.; Chen, F.-W. (Acta Phys.-Chim. Sin., 2014)

Gaussian 16, Revision A.03 (Gaussian, Inc., 2013)

(untitled) - Ernst, K.-H.; Böhringer, M.; McFadden, C. F.; Hug, P.; Müller, U.; Ellerbeck, U. (Nanotechnology, 1999)

(untitled) - Taniguchi, M.; Nakagawa, H.; Yamagishi, A.; Yamada, K. (Surf. Sci., 2000)

(untitled) - Taniguchi, M.; Nakagawa, H.; Yamagishi, A.; Yamada, K. (J. Mol. Catal. A: Chem., 2003)

(untitled) - Fasel, R.; Parschau, M.; Ernst, K.-H. (Angew. Chem., Int. Ed., 2003)

(untitled) - Fasel, R.; Parschau, M.; Ernst, K.-H. (Nature, 2006)

(untitled) - Lovinger, A. J.; Nuckolls, C.; Katz, T. J. (J. Am. Chem. Soc., 1998)

(untitled) - Li, P.; Lai, Y.; Wang, Y.; Qian, Y.; Duan, W.; Li, C.; Wang, Z.; Fang, Q.; Wang, H.; Tu, B.; Geng, Y.; Zeng, Q. (Sci. China: Chem., 2018)

(untitled) - Zhang, G.; Tan, J.; Zhou, L.; Liu, C.; Liu, J.; Zou, Y.; Narita, A.; Hu, Y. (Org. Lett., 2021)

(untitled) - Pieken, W. A.; Kozarich, J. W. (J. Org. Chem., 1989)

SADABS (University of Göttingen, 1996)

SHELXTL, Version 5.1 (Bruker Analytical Xray Systems, Inc., 1997)